The politics of deindustrialisation: the experience of the textiles and clothing sector (1974–1984). Issue 1 (April 2018) - Moraitis, Alexis
Abstract Deindustrialisation is taking an increasingly prominent place in public French discourses and has raised the question of the state's capacity to spur the country's industrial rejuvenation. This article views with scepticism the possibility for a state-led reindustrialisation as it finds that deindustrialisation has historically constituted an industrial strategy endorsed by French policy makers themselves. More precisely, this article argues that deindustrialisation is an industrial strategy that involves a state-sponsored disengagement from specific manufacturing activities in order to rationalise the sector and render it apt to confront international competition. This strategy, as it is argued, is conditioned by two main factors: the scarcity of resources that can potentially be distributed to industrial firms and secondly the resistance of workers and businesses in declining sectors that threaten the political legitimacy of governments. To illustrate this claim, the article proposes an examination of the Ministry of Industry's archives between 1974 and 1984 in order to trace the process industrial policy making enacted towards the textiles and clothing sector. It is found that the consecutive governments of the decade under examination pursued a targeted deindustrialisation of the sector while simultaneously devising strategies aimed at minimising the political costs of this policy preference on the governing authorities.